Writing Tasks In English Textbook On Cognitive Levels For Senior High School Grade Xii - M, Mardiah (Universitas Muhammadiyah Sumatera Utara, 2021)
The objective of this study was to investigate the levels of cognitive and their realization processes on writing tasks in the English textbook for Senior High School Grade XII based on revised version of Blooms Taxonomy. This study used descriptive qualitative approach. To collect the data, this research applied documentation technique. There were eighty writing tasks obtained from the English textbook published by Pusat Kurikulum dan Perbukuan, Balitbang, Kemdikbud. Those data were analyzed by applying Miles and Hubermanns (1994) analysis model including data reduction, data display and conclusion drawing. The research finding showed that the six levels of cognitive domain as proposed by Anderson and Kratwohl (2001) were realized on writing tasks in the English textbook published by Pusat Kurikulum dan Perbukuan, Balitbang, Kemdikbud. It was also found that the four types of writing tasks as proposed by Brown (2004) namely imitative, intensive, responsive and extensive were applied. So, it was concluded that the six levels of cognitive domains and the four types of writing tasks were realized totally in the English textbook.